Developing D–π–D hole-transport materials for perovskite solar cells: the effect of the π-bridge on device performance. (20th November 2020) - Ou, Yangmei; Sun, Anxin; Li, Haibei; Wu, Tai; Zhang, Dongyang; Xu, Peng; Zhao, Rongmei; Zhu, Liqiong; Wang, Runtao; Xu, Bo; Hua, Yong; Ding, Liming
Abstract : Three cost-effective D–π–D hole-transport materials were synthesized for use in perovskite solar cells. The (FAPbI3 )0.85 (MAPbBr3 )0.15 and CsPbI2 Br solar cells with SY3 gave PCEs of 19.08% and 13.41%, respectively. Abstract : Three cost-effective D–π–D hole transport materials (HTMs) with different π-bridges, including biphenyl (SY1 ), phenanthrene (SY2 ), and pyrene (SY3 ), have been synthesized via a one-pot reaction with cheap commercially available starting materials for application in organic–inorganic hybrid perovskite solar cells (PSCs). The effects of the various π-bridges on the photophysical, electrochemical, and electrical properties, and film morphologies of the materials, as well as on the photovoltaic properties of the PSCs, have been systematically investigated accordingly. Our results clearly show that HTM-SY3 with pyrene as the π-bridge exhibits higher hole mobility and better hole extraction/transport and film formation abilities than the other two HTMs. Devices that employed SY3 as the HTM show impressive power conversion efficiency (PCE) values of 19.08% and 13.41% in (FAPbI3 )0.85 (MAPbBr3 )0.15 - and CsPbI2 Br-based PSCs, respectively, which are higher than those of the reference HTM-SY1 - and SY2 -based ones. Our studies demonstrate a promising strategy to rationally design and synthesize low-cost and efficient HTMs through structural engineering for use in PSCs.